The Selection of an Interim CEO: Boundary Conditions and the Pursuit of Temporary Leadership - Mooney, Christine H.; Semadeni, Matthew; Kesner, Idalene F. (Journal of management, 2017)
More and more boards are tapping interim CEOs to temporarily fill the corner office. Prior research indicates the negative performance implications of this decision; yet, little is known about the rationale behind this decision. Our aim is to fill this research gap. Drawing on agency and human capabilities frameworks, we examined the contextual elements that influence a board’s decision to pursue temporary leadership. Within a sample of 375 successions occurring between 1998 and 2005, we found that boards of directors were more likely to select interim CEOs under certain succession conditions, namely, when the prior CEO was forced out and there was no heir apparent or when the prior CEO had served for a short tenure. Our results highlight the importance of context in succession selections and provide insights into why a board would pursue a decision with seemingly negative repercussions. Implications for theory and practice are discussed.